Alcohol and drug exposure in infants born to mothers prescribed methadone during pregnancy. (24th May 2012) - McGlone, L; Mactier, H; Cooper, G; Hassan, H
Abstract : Introduction: Adverse effects of in utero drug exposure include prematurity, IUGR and neurological and visual sequelae. Many of these problems are common to both drug and alcohol misuse. The extent of alcohol misuse during pregnancy in women who misuse drugs is unknown, and likely to be under-reported. The aims of this study were 1) to describe the incidence of in utero alcohol and illicit drug exposure in infants born to mothers prescribed methadone in pregnancy and 2) to compare the accuracy of confidential maternal interview with postnatal toxicology. Methods: Paired urine and meconium samples were collected within three days of birth from 56 infants born to mothers prescribed methadone during pregnancy. A confidential interview was conducted with all mothers within the same period. 45 mothers had had urine toxicology performed during pregnancy. Maternal and infant urine samples were screened using enzyme multiplied immunoassay techniques including methadone, opiates, benzodiazepines, amphetamines, cannabinoids and cocaine metabolites. Meconium samples were screened for the same drugs using ELISA; selected positive samples were further analysed using solid phase and liquid-liquid extraction followed by GC-MS or LC-MS-MS. The detection of elevated fatty acid ethyl esters (FAEEs), as a biomarker for significant prenatal alcohol exposure, was achieved using LC-MS-MS. Results: 47% (21/44) of infants tested had elevated FAEEs (> 10, 000 ng/g) indicating significant alcohol exposure during pregnancy. This was nine fold greater than the incidence of excess alcohol consumption reported by interview. Combining all toxicology results, 91% of infants (51/56) had been exposed to illicit drugs in utero, including opiates (73%), benzodiazepines (70%), cannabinoids (59%), amphetamines (7%) and cocaine (14%). Meconium analysis yielded more positive results than infant urine: illicit opiates (p<0.01), benzodiazepines (p=0.01), cannabinoids (p<0.01). Meconium analysis also yielded more positive results compared to interview for illicit opiates (p=0.03) and cannabinoids (p<0.01). Conclusion: The majority of infants born to mothers prescribed methadone during pregnancy are exposed to poly-substance misuse, and almost one half are additionally exposed to excess alcohol. This has implications for neuro-developmental follow up of this vulnerable cohort. Meconium analysis is more sensitive at detecting in utero drug exposure than maternal interview or infant urine toxicology.